Heritability of the HIV-1 reservoir size and decay under long-term suppressive ART - Chenjie Wan (Nature Portfolio, 2020)
The HIV reservoir is a major hurdle for a cure of HIV, but the factors determining its size and dynamics remain unclear. Here the authors show in a large cohort of 610 HIV-1 infected individuals, who are on suppressive ART for a median of 5.4 years, that viral genetic factors contribute substantially to the HIV-1 reservoir size.